Pengembangan Jobsheet Rangkaian Elektronika Kelas XI Teknik Elektronika Industri - Widyanto, Aditya Sunu; Priyanto, Priyanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
The purpose of this study is designed to: (1) develop Job sheet in accordance with the curriculum for Grade XI students of Electronic Engineering; and (2) describes the percentage level of job sheet worthiness as a learning device for implementing electronic circuits. This research is a development research using the development model of 4-D models with four main stages namely, Define, Design, Develop, Disseminate. Data collection was carried out using a questionnaire. The data analysis technique in this research is quantitative descriptive. The results of the study note that: (1) Job sheet was developed containing 13 materials; and (2) based on the results of the assessment of the media experts, the average percentage was 86.76% (very feasible), the material experts reached the average percentage of 81% (feasible), and the students got an average percentage score of 88.34% (very good). Although job sheets are considered appropriate and good for use in learning, there are some limitations regarding their application by teachers when teaching.